PENGARUH KESEJAHTERAAN TERHADAP KOMITMEN KERJA GURU DI TK KELURAHAN HARJOSARI KECAMATAN SUKAJADI KOTA PEKANBARU - Nurul Kintani Ishud; Wusono Indarto; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was aimed to know the effect of welfare towards the commitment of teachers working in kindergarten Village Harjosari Sukajadi District of Pekanbaru. This research was used quantitative research. The population of research as 122 people. Considering the large population, the determination of number the sample was done by using Solvin opinion in order to obtains a sample of 55 people. Data collection technique was used a questionnaire on the likert scale. Data analyzed technique simple linear regression techniques with statistical methods SPSS for Windows version 17. simple regression analysis is used to determine whether or not the effect of welfare on the commitment of teachers working in kindergarten Village Harjosari Sukajadi District of the city of Pekanbaru. Based on the research results obtained by value t count> t table (9775> 2007) then Ho is rejected, it means that there is a significant effect between the welfare of teachers with teachers' work commitments. So in this case can be concluded that the welfare of teachers affect the commitment of the teachers working in kindergarten Village Harjosari Sukajadi District of the city of Pekanbaru. Determinant coefficient value (R Square) of 0643. This means that the influence of teachers' welfare to work commitment of teachers in kindergarten Village Harjosari Sukajadi District of Pekanbaru City amounted to 64.3% while the remaining amount (100% - 64.3 = 35.7%) is influenced by other variables that are outside of a teacher's welfare variables.Keywords : Welfare, Work Commitment